Specific Ultrasound Pattern of Perinatal Torsioned Ovarian Cysts: Sonographic-pathologic Correlation - Seyed Ali Alamdaran; Nona Zabolinejad; Lida Jarahi; Maryam Tavakoli; Fariborz Azizi; Mohammad Yekta; Ali Feyzi (Mashhad University of Medical Sciences, 2020)
Background: The accurate differentiation of perinatal torsioned ovarian cysts (PTOCs) in neonates is of utmost importance. This importance is due to the fact that if PTOCs are diagnosed properly, minimally invasive or conservative management approaches can be offered. The present study aimed to describe the ultrasound findings of PTOCs and compare the results with pathological findings. Methods: This prospective cross-sectional study was conducted in Mashhad University of Medical Sciences, Mashhad, Iran, within 2014-2019. All infants with an intra-peritoneal cyst underwent meticulous ultrasound examination. Patients were followed up until reaching the final diagnosis. In surgically approved PTOCs, the correlation between sonographic and pathologic findings was examined. Results: Twenty two cases (aged 2 days to 6 months, mean age = 6 weeks) with PTOC were diagnosed during this time. Cysts were mainly on the right side (86%) with mean diameter of 51 mm (27-73mm). The ultrasonogrphic signs of fluid debris level, triple-layer wall and wrinkled inner layer were observed in almost all of patients. The pathologic triple-layer of perinatal torsioned ovarian cysts included necrotic content with granulation, stroma, and epithelium layers was observed by ultrasound as a uni-locular cyst containing fluid debris level with an echogenic wrinkled inner layer, a hypoechoic uneven non-uniform middle layer and echogenic outer epithelial surface. Conclusion: Sonographically detected triple-layered pattern for PTOCs was completely in agreement with pathologic results. Then, this specific ultrasound pattern is pathognomonic for PTOC.